Electron microscopy images reveal magnetic properties - Coughlin, Kirk; Bouc, Matthew; Yungbauer, Thomas; Buelke, Chris (My University, 2013)
Nanoalloys are a fairly new and highly appealing topic of study. Research has shown that different properties and characteristics may be found by adjusting the size and compositional differences during manufacturing. These alloy mixtures may yield unique, consistent nanoalloys that meet or exceed the desired effects, or show properties in common with different nanoalloys with similar crystal structures. Electric, thermodynamic, and magnetic applications are just some of the different areas that can be changed due to fine tuning a nanoalloy's size and composition. Nanomagnets are one of the next big investments in the electronic world. Current applications include high-energy-product permanent magnets, hard disk storage technology, and innovations in the field of medicine. It is well known that transistors have rapidly shrunk in size over the past few decades. However, shrinking the size of usable magnets has been difficult. Currently, there is a large field of research that seeks to find affordable, powerful, and effective nanosized magnets. A procedure for characterization of nanomaterials was established, including determining the spacing between planes of atoms in a nanomagnet to determine its crystal structure as well as comparing properties of nanomagnets with different elemental combinations.
Keywords: Nanostructures; Magnets; Nanomagnets; Magnetic properties; HRTEM; Nanostructured materials -- Magnetic properties